Thermodynamic and environmental considerations of small turbojet engine under different design variables - Aygun, Hakan (Taylor & Francis Inc, 2024)
Aviation activities have jeopardized the limited energy sources and thereby environmental sustainability due to fossil fuel consumption. Therefore, aircraft engines being the significant emission source have attracted the attention of engineers toward improvement of the design process. In this study, turbojet engine (TE) and its components were examined with exergy, environmental, and sustainability metrics. Then, the effects of several design variables such as turbine inlet temperature (TIT) ranging between 850 K and 1100 K and compressor pressure ratio (CPR) ranging between 3 and 4 on exergetic and environmental parameters were investigated. As a novelty, a new index named specific irreversibility production (SIP) was improved. According to exergy assessment, the wasted exergy ratio (WExR) of the combustor was found as highest changing between 42.46% and 51.89%. Moreover, exergy efficiency of the turbojet engine was determined between 16.42% and 21.92%. According to environmental assessments, the ecological effect factor (EcoEF) of the TE was computed between 4.77 and 6.08 under ranges of different design variables. Finally, the SIP of turbojet was gauged between 0.488 MW/kN and 0.586 MW/kN. Considering these results, the TIT and CPR have high effect on the optimum engine performance and environmental parameters.
Keywords: Turbojet; exergy; design variables; environmental indicators; thermodynamics